Effects on Volunteer Peer Leaders Participating in a Health Promotion Program for U.s. Veterans - (:unkn) unknown (My University, 2013)
Health-focused peer-led interventions demonstrate success in reducing risk-related behaviors among participants with chronic illnesses, yet few researchers have explored the effects of such interventions on the health of volunteer peer leaders who participate in the interventions. Using data from the project entitled, An RCT of a Peer Support Intervention to Improve Hypertension, this study explored volunteer peer leaders' self-care behaviors that contribute to blood pressure control in two hypertension interventions for U.S. veterans. Inspection of the study's findings demonstrated that volunteer peer leaders improved their health habits and hypertension knowledge significantly more than the peer groups they served. Findings revealed no significant differences between the two types of peer leader interventions. The results of this study confirm previous research conducted in the field of volunteerism, peer support, group learning and health behavior change from the context of a veteran population. Future research is needed to extend the study's findings to additional groups, settings, geographic areas and with other disease conditions and illnesses.
Keywords: Chronic Disease; Community Engagement; Health Behavior; Peer Leaders; Self-managemenet